0018 Validation of a wearable real-time monitor of exposure to naphthalene. (23rd June 2014) - Proctor, Susan; Snawder, John; Johnson, Belinda; Maule, Alexis; Winkler, Amanda; Muruganandham, M; Suri, R; Hulla, Janis
Abstract : Objectives: Direct reading instruments are valuable tools for assessing exposure in the workplace. Adaption of such instruments to serve as valid and efficient tools to provide personal exposure data for environmental surveillance and occupational epidemiology studies fulfils a critical research need. Method: A project is underway to validate new sensor technology that utilises native fluorescence of molecules excited by ultraviolet light with the goal of delivering laboratory-quality data for qualitative and quantitative analyses. The initial chemical of focus with this technology is naphthalene. The project is proceeding in two stages: independent laboratory validation and an exposure assessment field study, which is being conducted in two Phases: Phase I examines the degree to which the instrument serves as a sensor of naphthalene by assessing the concordance between measured personal air levels and those measured with conventional technologies e.g. active samplers; Phase II evaluates the validity of the instrument to serve as a dosimeter, correlating instrument-measured naphthalene levels in air with biological markers of exposure from skin, urine and exhaled breath. Results: Independent laboratory evaluations indicate the instrument is accurate within accepted laboratory guidelines, when compared to standard gas chromatography methods. Results from the Phase I field study with US military personnel working with jet propulsion fuels (e.g., JP8 and jet A) as part of their regular work responsibilities support laboratory validation findings. Phase II data efforts are in progress. Conclusions: This technology permits real-time evaluation of task-specific variations in personal naphthalene exposure levels, data that are currently not available with conventional active sampling processes.